2021
DOI: 10.1002/csr.2106
|View full text |Cite
|
Sign up to set email alerts
|

Corporate social responsibility corporate innovation: A cross‐country study of developing countries

Abstract: This paper explores the relationship between corporate social responsibility, corporate innovation, and corporate performance in developing countries. Firm level governance and corporate social responsibility data for 150 companies from 12 developing countries were collected from Datastream and Bloomberg for 2014-2019. The results show that in the context of developing countries there is no significant relationship between corporate social responsibility and corporate innovation. Our findings raise concerns ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 44 publications
0
25
1
1
Order By: Relevance
“…Finally, this paper also contributes to the studies on the relationship between CSR and innovation in developing countries. Differing from previous findings of no relationship between CSR and innovation in developing countries [5], our study shows that certain categories of CSR have a significant positive impact on innovation in China. This provides different empirical evidence for understanding the relationship between CSR and innovation in developing countries.…”
Section: Introductioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Finally, this paper also contributes to the studies on the relationship between CSR and innovation in developing countries. Differing from previous findings of no relationship between CSR and innovation in developing countries [5], our study shows that certain categories of CSR have a significant positive impact on innovation in China. This provides different empirical evidence for understanding the relationship between CSR and innovation in developing countries.…”
Section: Introductioncontrasting
confidence: 99%
“…Ecological investments in the environment weaken the R&D effect because managers' attention to innovation can be undermined by their emphasis on environment-related CSR. Furthermore, using data from 150 companies in 12 developing countries, Ullah and Sun [5] find no significant relationship between CSR and innovation in developing countries.…”
Section: Literature Review and Research Hypothesesmentioning
confidence: 95%
See 1 more Smart Citation
“…As our previous review has shown, there are clear regional differences in studies on company sustainability. In particular, the Latin American area is deficient in studies that address business sustainability (Crane & Glozer, 2016; Lizarzaburu & Del Brio, 2016; Ocampo López et al, 2016; Sierra‐García et al, 2014; Ullah & Sun, 2021) What can condition the achievement of the SDGs established in the 2030 agenda (UN, 2015), as indicated by Han and Lee (2021).…”
Section: Future Lines Of Researchmentioning
confidence: 99%
“…In principle, however, the company is always seen as a body that is not isolated from the environment but interacts with society. This relationship brings rights and obligations to this society, and it should lead not only to economic growth but also to an increase in quality of life (Ullah & Sun, 2021). This can help a company to succeed commercially.…”
Section: Introductionmentioning
confidence: 98%